Photon-counting computed tomography: clinical application in oncological, cardiovascular, and pediatric radiology = Photon-Counting Computertomographie : klinische Anwendungen in der onkologischen, kardiovaskulären und pädiatrischen Radiologie - Hagen, Florian; Soschynski, Martin; Weis, Meike; Hagar, Muhammad Taha; Krumm, Patrick; Ayx, Isabelle; Taron, Jana; Krauss, Tobias; Hein, Manuel; Ruile, Philipp; von zur Muehlen, Constantin; Schlett, Christopher L.; et al. (RöFo, 2023)
Background Photon-counting detector computed tomography (PCD-CT) is a promising new technology with the potential to fundamentally change workflows in the daily routine and provide new quantitative imaging information to improve clinical decision-making and patient management. - Method The contents of this review are based on an unrestricted literature search of PubMed and Google Scholar using the search terms “photon-counting CT”, “photon-counting detector”, “spectral CT”, “computed tomography” as well as on the authors’ own experience. - Results The fundamental difference with respect to the currently established energy-integrating CT detectors is that PCD-CT allows for the counting of every single photon at the detector level. Based on the identified literature, PCD-CT phantom measurements and initial clinical studies have demonstrated that the new technology allows for improved spatial resolution, reduced image noise, and new possibilities for advanced quantitative image postprocessing. - Conclusion For clinical practice, the potential benefits include fewer beam hardening artifacts, a radiation dose reduction, and the use of new or combinations of contrast agents. In particular, critical patient groups such as oncological, cardiovascular, lung, and head & neck as well as pediatric patient collectives benefit from the clinical advantages.